AB0260 Association between anti-citrullinated protein antibody status, erosive disease and healthcare resource utilisation in patients with ra. (12th June 2018) - Harrold, L.R.; Guo, L.; Connolly, S.E.; Alemao, E.; Rebello, S.; Shan, Y.; Kremer, J.M.
Abstract : Background: Anti-citrullinated protein antibody (ACPA) is a highly specific biomarker for RA 1 and ACPA-seropositive patients have a tendency toward severe erosive disease and more rapid disease progression. 2–4 Little is known regarding the impact of poor prognostic factors, such as ACPA and erosive disease, on healthcare resource utilisation (HCRU). Objectives: To characterise the rate of HCRU between anti-cyclic citrullinated peptide (anti-CCP; a surrogate of ACPA) positive (+) patients with or without erosions who initiated biologic (b)DMARD treatment. Methods: This analysis included patients aged ≥18 years, who were enrolled in a large sequential RA registry (October 2001–August 2017) and who had known erosions, as measured by radiography, and anti-CCP +status at or prior to bDMARD initiation visit and a 12 month (±3 months) follow-up visit. Anti-CCP +was defined as ≥20 U/mL. Rates of HCRU, including all-cause hospitalizations, all joint surgeries (total and partial; all sites), radiographic procedures and use of assistive devices, were estimated over 12 months of follow-up from the bDMARD initiation visit in anti-CCP +patients with or without erosions. Rates of HCRU per 100 patient-years and risk ratios, adjusted by baseline age, were estimated with 95% CI using a Poisson regression model. Results: A total of 2047 anti-CCP +patients were included in this analysis, 868 with and 1179 without erosions. At biologic initiation visit, mean (SD) age was 58.9 (12.5) and 55.9 (12.5) years and disease duration was 11.7 (10.1) and 6.4 (7.5) years, respectively, in anti-CCP +patients with and without erosions. Over 12 months of follow-up, the rates of HCRU were higher among anti-CCP +patients with versus those without erosions at baseline bDMARD initiation visit (table 1). Conclusions: ACPA seropositivity with erosive disease predicts high utilisation of healthcare resources, suggesting that early therapeutic intervention may be warranted in anti-CCP +patients to achieve better disease control and reduce the complications from RA. References: [1] Scott DL, et al. Lancet2010;376:1094–108. [2] van der Helm-van Mil AH, et al. Arthritis Res Ther2005;7:R949–58. [3] Hecht C, et al. Ann Rheum Dis2015;74:2151–6. [4] Harrold LH, et al. Arthritis Rheumatol2017:69(S10):499. Disclosure of Interest: L. Harrold Shareholder of: Corrona, LLC, Grant/research support from: Pfizer, Consultant for: Roche, Bristol-Myers Squibb, L. Guo: None declared, S. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Rebello Employee of: Corrona, LLC, Y. Shan Employee of: Corrona, LLC, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: AbbVie, Bristol-Myers Squibb, Genentech, Lilly, Novartis, Pfizer, Employee of: Corrona, LLC